Magnetic Resonance Imaging Predicts Histopathological Composition of Ileal Crohn's Disease. (2nd January 2018) - Wagner, Mathilde; Ko, Huaibin Mabel; Chatterji, Manjil; Besa, Cecilia; Torres, Joana; Zhang, Xiaofei; Panchal, Hinaben; Hectors, Stefanie; Cho, Judy; Colombel, Jean-Frederic; Harpaz, Noam; Taouli, Bachir
Abstract: Background and Aims: Recently, smooth muscle hypertrophy has been suggested to be a contributor to small bowel lesions secondary to Crohn's disease [CD], in addition to inflammation and fibrosis. Here, we assess the value of magnetic resonance imaging [MRI] for the characterisation of histopathological tissue composition of small bowel CD, including inflammation, fibrosis, and smooth muscle hypertrophy. Methods: A total of 35 consecutive patients [male/female 17/18, mean age 33 years] with ileal CD, who underwent small bowel resection and a preoperative contrast-enhanced MRI examination within 1 month before surgery, were retrospectively included. Image assessment included qualitative [pattern/degree of enhancement, presence of ulcerations/fistulas/abscesses] and quantitative parameters [wall thickness on T2/T1-weighted images [WI], enhancement ratios, apparent diffusion coefficient [ADC], Clermont and Magnetic Resonance Index of Activity [MaRIA] scores). MRI parameters were compared with histopathological findings including active inflammation, collagen deposition, and muscle hypertrophy using chi square/Fisher or Mann-Whitney tests and univariate/multivariate logistic/linear regression analyses. Results: Forty ileal segments were analysed in 35 patients. Layered pattern at early-post-contrast phase was more prevalent (odds ratio [OR] = 8; p = 0.008), ADC was significantly lower [OR = 0.005; p = 0.022], and MaRIA score was significantly higher [OR = 1.125; p = 0.022] in inflammation grades 2–3 compared with grade 1. Wall thickness on T2WI was significantly increased [OR = 1.688; p = 0.043], and fistulas [OR = 14.5; p = 0.017] were more prevalent in segments with disproportionately increased muscle hypertrophy versus those with disproportionately increased fibrosis. MaRIA/Clermont scores, wall thickness on T1WI and T2WI, and ADC were all significantly correlated with degree of muscular hypertrophy. Conclusions: MRI predicts the degree of inflammation, and can distinguish prominent muscle hypertrophy from prominent fibrosis in ileal CD with reasonable accuracy (area under receiver operating characteristic curve [AUROC] > 0.7).